2014
DOI: 10.5005/jp-journals-10036-1004
|View full text |Cite
|
Sign up to set email alerts
|

TG/HDL-C Ratio: A Surrogate Marker of Insulin Resistance in Patients with Metabolic Syndrome

Abstract: Insulin resistance (IR) is hallmark of metabolic syndrome. It is important to identify IR as it is the early stage before development of diabetes mellitus. The standard method to measure insulin resistance is the euglycemic clamp technique, which is laborious. Hence, a number of surrogate measures like homeostasis model assessment of insulin resistance (HOMA-IR), quantitative insulin sensitivity check index (QUICKI) and triglyceride/high density lipoprotein cholesterol (TG/HDL-C) ratio have been developed. Bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Insulin resistance does not always involve the high concentration of blood glucose according to the results by Fujii et al [18], Samant et al [26], and Yin et al [42]. The results reported by Fujii et al [18] and Samant et al [26] suggested that patients with possible insulin resistance defined by HOMA-IR ≥ 2.5 [19] were not in the condition of high blood glucose, but the patients with diabetes were in the condition of high blood glucose [18]. The blood glucose levels 109.4 ± 1.5 mg/dL [18] and 113 ±1.19 mg/dL [26] were reported for the subjects (N = 71) classified as impaired glucose tolerant (IGT) with HOMA-IR 2.7 ± 0.3 [18] and the subjects (N = 60) classified as metabolic syndrome group with TG/HDL-C ratio 4.554 ± 0.152 and HOMA-IR 6.14 ± 0.09 [26].…”
Section: Relation Between Insulin Resistance and Blood Glucose Levelsmentioning
confidence: 95%
See 4 more Smart Citations
“…Insulin resistance does not always involve the high concentration of blood glucose according to the results by Fujii et al [18], Samant et al [26], and Yin et al [42]. The results reported by Fujii et al [18] and Samant et al [26] suggested that patients with possible insulin resistance defined by HOMA-IR ≥ 2.5 [19] were not in the condition of high blood glucose, but the patients with diabetes were in the condition of high blood glucose [18]. The blood glucose levels 109.4 ± 1.5 mg/dL [18] and 113 ±1.19 mg/dL [26] were reported for the subjects (N = 71) classified as impaired glucose tolerant (IGT) with HOMA-IR 2.7 ± 0.3 [18] and the subjects (N = 60) classified as metabolic syndrome group with TG/HDL-C ratio 4.554 ± 0.152 and HOMA-IR 6.14 ± 0.09 [26].…”
Section: Relation Between Insulin Resistance and Blood Glucose Levelsmentioning
confidence: 95%
“…Insulin resistance does not always involve the high concentration of blood glucose according to the results by Fujii et al [18], Samant et al [26], and Yin et al [42]. The results reported by Fujii et al [18] and Samant et al [26] suggested that patients with possible insulin resistance defined by HOMA-IR ≥ 2.5 [19] were not in the condition of high blood glucose, but the patients with diabetes were in the condition of high blood glucose [18].…”
Section: Relation Between Insulin Resistance and Blood Glucose Levelsmentioning
confidence: 96%
See 3 more Smart Citations